Overview of academic production in high abilities/giftedness - Pedro, Ketilin Mayra [UNESP]; Martins, Barbara Amaral [UNESP]; Silva, Rosilaine Cristina da [UNESP]; Marques Ogeda, Clarissa Maria [UNESP] (Organizacion Estados Iberoamericanos Educacion Ciencia & Cultura-oei, 2016)
The Special Education includes disabilities, global developmental disorders and high ability/giftedness. We had high ability/giftedness as research focus and we aimed to develop an overview of theses and dissertations in the area, checking what themes poorly investigated, as well as those who are already sufficiently explored. For this, we consulted the bank of theses and dissertations of Coordenacao de Aperfeicoamento de Pessoal de Nivel Superior, the Biblioteca Digital Brasileira de Teses e Dissertacoes and the main Graduate Programs in Special Education. Were located 126 productions, from 1987 to 2014. Based on the analysis of title, abstract and keywords, we meet 17 thematic categories. Since 2000 there has been a significant increase in production, however, many important questions remain lacking investigations.
Keywords: special education; high ability / giftedness; scientific production